Potencialidades turísticas eco esportivas na região das águas termais no estado de Goiás - Sousa, Diego Pericles Rodrigues de (2018)
The cities of Caldas Novas and Rio Quente, which arelocated in the south of Goiás form the Region of Hot Waters, which stands out as the main tourist pole of the State, due to its hot springs. Although mass tourism has established itself around urban thermalism, its tourist potential unfolds beyond these structures and its thermal springs, since there are innumerable potentialities and attractions that are unknown to tourists who visit the region. In this context, we seek to identify and make explicit the eco-tourism potential of the region, in order to propose its diversification and expansion through eco-sports activities, focusing on environmental and socioeconomic sustainability of the region and, consequently, by tourism itself, which is the direct and indirect economic maintainer of the Region of the Hot Waters.